Impacts of the COVID-19 pandemic on cardiopulmonary resuscitation (Research, Society and Development, 2023)
Introduction: The COVID-19 virus has high transmissibility, which has resulted in a pandemic scenario. Within this context, cardiopulmonary resuscitation is an example of a procedure that was affected, since it involves close contact of the patient with the professional, which increases the risk of infection of those involved. Objective: to analyze and gather which were the impacts of the pandemic on cardiopulmonary resuscitation. Methodology: this is an integrative review of the literature, guided by the PICO strategy that started from the clinical question: "How did the COVID-19 pandemic impact cardiopulmonary resuscitation (CPR)?". The databases used were Virtual Health Library (VHL), Scientif Eletronic Library Online (SciELO), National Library of Medicine (PubMed) and Google Scholar. Results and discussion: The SARS-CoV-2 virus has a high transmissibility, which resulted in the reformulation of procedures to ensure the safety of professionals. Furthermore, cardiac arrest occurring inside the hospital environment was related to greater severity of the patients, which generated worse survival outcomes. Out-of-hospital cardiac arrests were impacted by delayed emergency care and fear of infection by bystanders. Conclusion: The COVID-19 pandemic impacted cardiopulmonary resuscitations in several ways, and the outcomes of this interaction were not positive. Thus, it was perceived that the education of professionals and of the general population was of extreme importance for better choices to be made. Thus, knowing the impacts of the pandemic is important to better deal with the issue in focus and to serve as an example for new aggravations.